Ánforas vinarias de Hispania citerior-Tarraconensis (s.Ia.C.-Id.C.) : caracterización arqueométrica - Martínez Ferreras, Verònica (Roman and late antique Mediterranean pottery, 2014)
This volume presents the results of a multidisciplinary archaeological and archaeometric study of the wine amphorae produced in Hispania Citerior (Tarraconensis, in Augustus' reorganisation) between the first century BC and the first century AD